PESANTREN BETWEEN GLOBALIZATION AND POLITIZATION: Maduranese Pesantren After the Fall of New Order (1998-2007) - Fathol Haliq (Asia-Pacific Journal on Religion and Society, 2021)
After the fall of the Soeharto regime, there has been political euphoria and paradoxical strategies, between populist idealism and political pragmatism. Political pragmatism leaves acute problems in the world of pesantren. Culture-shock, the unpreparedness of pesantren leadership transformation led to a number of interesting strategies from the elders to give the mandate to the young keyae. In this context, there is a tug of war between change and status quo, idealism and educational pragmatism, so that the globalization agenda is not answered anticipatively and progressively. The strategy carried out by pesantren seems unsustainable, broken, pragmatic, and only answers a momentary agenda. On the other hand, pesantrens answer international problems - problems of human rights, humanity, poverty, environment, and global political economy - with steps that are typical of pesantrens, namely "pesantren cultural politics" and community empowerment. The pesantren community argues that moving locally answers global problems. Because the issue of globalization is very close to the pesantren community which covers the community around the pesantren.  Here, the face of globalization is "subdued" with a religious cultural identity that is progressive, pluralist, and sides with weak communities. Not only is the pesantren an agent of globalization, it also reproduces globalization into an empowering face for the community with a pesantren cultural identity. This empowering face can be seen in the empowerment model, at the end of this paper.